An education tool study on mechatronics: Emulation of stepper motor driving systems by using a microcontroller based system interface - (:unkn) unknown (IEEE, 2004)
Some type of electromechanical actuator related driving systems, such as stepper motor driving systems, have various type of implementations in the mechatronic systems. Besides the implementation variety, rapid changes in the actuator and driver technologies make it a costly and difficult task training about the such type of mechatronic systems. It is most acute for undergraduate programs, specially. However, with the introduction of computers and flexible programming techniques, it is now possible to simulate these systems easily. Systems can also be emulated economically in this way. Then fore, electromechanical actuator related mechatronic systems can be teached and/or trained, by computer simulations andlor emulations. This paper describes such a teaching and training tool study on stepper motor driving systems, including full-step, half-step and micro-step driving implementations. System emulations are fulfilled by using a microcontroller based system interlace, in the study.